From conventional to organic peanut farming Preliminary on-farm field experiments in My Loi Climate-Smart Village, Ha Tinh province, Vietnam - Le Thi Tam; Bui Tan Yen; Simelton, Elisabeth; Le Dinh Hoa; Nguyen Thi Toan; Nguyen Thi Giang (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This document summarizes the findings of participatory organic peanut experiment with three households in My Loi Climate-Smart Village in 2019, funded by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS).